Mineral reactivity modulates the effect of organic matter addition on phosphorus solubility in tropical volcanic soils - Méndez Fernández, Juan Carlos (2024)
The aim of this study was to analyze how mineral reactivity modulates the effect of adding an organic amendment on the solubility, adsorption, and use efficiency of phosphorus (P) in tropical volcanic soils. Two Andisols from Costa Rica with a lower (LR) and a higher (HR) mineral reactivity were selected. In an incubation experiment, the solubility of two fractions of native P (measured as P-Olsen and P-CaCl2) was analyzed after the addition of compost. Phosphate (PO4) adsorption isotherms were determined for soils preincubated with compost and the results were interpreted using the Langmuir equation and the mechanistic Charge Distribution (CD) model. A greenhouse bioassay was conducted to investigate the impact of compost addition on the agronomic efficiency of P (AEP), using sorghum (Sorghum bicolor) as a reference plant species. Compost addition initially increased P-Olsen concentrations after 14 days of incubation, but after 28 days, P-Olsen levels decreased, suggesting re-adsorption of PO4 on the mineral surfaces. Compost addition did not significantly affect the concentration of P-CaCl2 in the HR soil but increased it in the LR soil. Furthermore, increasing the amount of added compost decreased the maximum P binding capacity (Qmax) of the HR soil. In the LR soil, Qmax values did not significantly change with further addition of compost above 5%, indicating potential saturation of P binding sites. The addition of compost improved the AEP only in the HR soil. In the LR soil, changes in AEP were measured at the highest P dose, regardless of the compost addition. Organic amendments can reduce the P adsorption and enhance use efficiency of P fertilizers by competing with PO4 for binding sites on minerals surfaces of tropical volcanic soils. However, this interaction is modulated by the mineral reactivity of the soil. Increasing organic matter inputs is an alternative to improve AEP, particularly in soils with higher P binding capacity.